Miss Nelson is back - Allard, Harry; Marshall, James, 1942-1992 (Boston, Massachusetts : Houghton Mifflin Co., 1982)
When their teacher has to go away for a week, the kids in room 207 plan to "really act up."
G2
Keywords: Schools -- Fiction; Teachers -- Fiction